Sustained Release Matrix Metoprolol Tartrate with Inlay Hydrochlorothiazide Tablet - AR Mullaicharam; Ph.Maisa Shummo; P.Muthuprasanna (International Journal of Pharma and Bio Sciences, 2010)
The objective of the present study was to develop once-daily sustained release matrix tablets of metoprolol tartrate with inlay hydrochlorothiazide tablet as an immediate release formulation. The inlay tablets were prepared by wet granulation method using hydroxy propyl methylcellulose in various percentages. The drug-excipient incompatibility studies were performed by Differential Scanning Calorimetry(DSC).The granules showed satisfactory flow properties and compressibility. Five trial batches were prepared using various excipients. The trial batch M4(35% hydroxy propyl methyl cellulose) could extend the release of metoprolol tartrate for 24h and that of hydrochlorothiazide for 2h, which matched with the USP drug profile. The in vitro and the in vivo release studies in rabbit were performed. The mechanism of drug release was diffusion coupled with erosion. The stability studies were performed on trial batch M4 which were kept at 40°C and 75%Relative humidity for 90days and the product was evaluated every 30 days.